Navigating Learner Differences in Secondary Level English Classrooms - Bhandari, Harischandra (English Language Teaching Perspectives, 2024)
The purpose of this article is to explore the teachers’ perceptions on different aspects of learner differences and managing such differences in the secondary level English Language Education (ELE) classrooms. The explored perceptions have been thematically presented on seven major aspects of classroom learner differences such as: age, intelligence, learning styles, learning strategies, motivation, personality, and norms, values and beliefs that cause differences as an issue have been realized along with concept of inclusive education as an approach to deal with learners in the classroom. Such differences as an issue can be softened by raising awareness among the students, so that they will realize their own as well as other fellow’s characteristics. As this article is based on phenomenological research approach, four different secondary level English language teachers, with at least more than five years’ teaching experiences, were interviewed and the data have been analyzed thematically, and interpreted. The result shows that learner differences exist in the school classrooms of highly dense urban areas. These differences in the classroom can create complexities for teachers in teaching language courses in foreign context. However, by understanding the concept of inclusive education, teachers can include varieties of students without any bias in a single classroom and teach in a better way.